MECHANISMS OF STATE REGULATION OF INNOVATIVE DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP IN THE CONTEXT OF EUROPEAN INTEGRATION: THE EXPERIENCE OF SWEDEN - Gura, Viktoriya (Public Management and Policy, 2026)
The article examines the mechanisms of state regulation of the innovative development of social entrepreneurship in the context of European integration, using Sweden as a case study. The relevance of the research is determined by the need to strengthen the capacity of social enterprises to respond to complex socio-economic challenges, including social exclusion, unemployment, regional disparities, limited access of vulnerable groups to labour markets, and the need for sustainable post-war recovery in Ukraine. The study argues that the Swedish model of public support for social entrepreneurship is not based on a single comprehensive framework law on the social economy. Instead, it functions through a multi-level combination of strategic policy instruments, legal visibility mechanisms, innovation funding, public procurement tools, regional development measures, cooperation between state agencies and municipalities, and targeted support for work integration social enterprises. Particular attention is paid to the 2018 Swedish strategy for social enterprises and social innovation, the special register of idea-based organisations introduced under Act 2022:900, the role of the Swedish Agency for Economic and Regional Growth, the Swedish Innovation Agency Vinnova, the National Agency for Public Procurement, the Public Employment Service, municipalities, regions, civil society organisations and social innovation platforms. The article also analyses Sweden’s innovation environment, which is characterised by a high level of research and development expenditure, developed institutional cooperation and a strong role of civil society in welfare provision. It is shown that the Swedish experience is especially relevant for Ukraine because it demonstrates how social entrepreneurship can be integrated into broader public policies without isolating it from innovation, employment, regional development, public services and European social economy priorities. The article proposes directions for adapting the Swedish model to Ukrainian conditions, including institutional recognition of social entrepreneurship, a transparent registry, targeted access to public support instruments, development of social procurement, stimulation of innovation ecosystems, and introduction of social impact measurement. The study concludes that the Swedish experience may serve as a practical reference point for Ukraine in the process of European integration, provided that its instruments are adapted to national legal, financial and administrative realities.